Foundations of intelligent systems : 22nd international symposium, ISMIS 2015, Lyon, France, October 21-23, 2015, proceedings /: 22nd international symposium, ISMIS 2015, Lyon, France, October 21-23, 2015, proceedings. (2015) - Unknown
No abstract available